Culture and Household Decision Making: Balance of Power and Labor Supply Choices of US-born and Foreign-born Couples - Sonia Oreffice (Institute for the Study of Labor (IZA), 2014)
This study investigates how spouses' cultural backgrounds mediate the role of intra-household bargaining in the labor supply decisions of foreign-born and US-born couples, in a collective-household framework. Using data from the 2000 US Census, I show that the hours worked by US-born couples, and by those foreign-born coming from countries with gender roles similar to the US, are significantly related to common bargaining power forces such as differences between spouses in age and non-labor income, controlling for both spouses' demographic and socioeconomic characteristics. Households whose culture of origin supports strict and unequal gender roles do not exhibit any association of these power factors with their labor supply decisions. This cultural asymmetry suggests that spousal attributes are assessed differently across couples within the US, and that how spouses make use of their outside opportunities and economic and institutional environment may depend on their ethnicities.
Keywords: D1; J15; J22; 330; household bargaining power; gender roles; culture; labor supply